SgNramp1, a plasma membrane-localized transporter, involves in manganese uptake in Stylosanthes guianensis - Zou, Xiaoyan; Huang, Rui; Wang, Linjie; Wang, Guihua; Miao, Ye; Rao, Idupulapati; Liu, Guodao; Chen, Zhijian (Frontiers in Plant Science, 2022)
Transporters belonging to the natural resistance-associated macrophage protein (Nramp) family play important roles in metal uptake and homeostasis. Although Nramp members have been functionally characterized in plants, the role of Nramp in the important tropical forage legume Stylosanthes guianensis (stylo) is largely unknown. This study aimed to determine the responses of Nramp genes to metal stresses and investigate its metal transport activity in stylo. Five SgNramp genes were identified from stylo. Expression analysis showed that SgNramp genes exhibited tissue preferential expressions and diverse responses to metal stresses, especially for manganese (Mn), suggesting that the involvement of SgNramps in the response of stylo to metal stresses. Of the five SgNramps, SgNramp1 displayed the highest expression in stylo roots. A close correlation between SgNramp1 expression and root Mn concentration was observed among nine stylo cultivars under Mn limited condition. The higher expression of SgNramp1 was correlated with a high Mn uptake in stylo. Subsequent subcellular localization analysis showed that SgNramp1 was localized to the plasma membrane. Furthermore, heterologous expression of SgNramp1 complemented the phenotype of the Mn uptake-defective yeast (Saccharomyces cerevisiae) mutant Δsmf1. Mn concentration in the yeast cells expressing SgNramp1 was higher than that of the empty vector control, suggesting the transport activity of SgNramp1 for Mn in yeast. Taken together, this study reveals that SgNramp1 is a plasma membrane-localized transporter responsible for Mn uptake in stylo.